2015
DOI: 10.1007/s00520-015-2964-6
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction defects are seen in the buccal mucosa of patients receiving standard dose chemotherapy for cancer

Abstract: Tight junction defects are seen in the buccal mucosa of patients receiving standard dose chemotherapy for cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This protective effect on the keratinocyte barrier integrity is probably related to the ability of TFs to inhibit P. gingivalis gingipains . Additionally, black tea TFs could reduce the expression of epithelial cell‐derived MMPs, which could also be involved in the damage of the barrier integrity, as previously reported .…”
Section: Discussionsupporting
confidence: 63%
“…This protective effect on the keratinocyte barrier integrity is probably related to the ability of TFs to inhibit P. gingivalis gingipains . Additionally, black tea TFs could reduce the expression of epithelial cell‐derived MMPs, which could also be involved in the damage of the barrier integrity, as previously reported .…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, DS exerts functions in extracellular matrix assembly, fibroblast activity and wound repair processes [19, 2931]. Therefore, DS treatment could effectively modify various radiation-induced or -altered cellular or cell-matrix interactions [32–34]. To date, clinical applications of DS are scarce, although several preclinical and clinical studies revealed an array of potential indications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, they are highly plastic structures vulnerable to post‐transcriptional and ‐translational modification by a variety of pathological cues . Tight junction disruption has been identified following treatment with a number of chemotherapeutic agents, both preclinically and clinically . To date, many studies have shown architectural abnormalities, and functional alteration, of key tight junction proteins such as claudin‐1, ZO‐1 and occludin.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Tight junction disruption has been identified following treatment with a number of chemotherapeutic agents, both preclinically 35,36 and clinically. [37][38][39] To date, many studies have shown architectural abnormalities, and functional alteration, of key tight junction proteins such as claudin-1, ZO-1 and occludin. As such, the current study focused on these three proteins, despite the numerous other proteins present within the junctional complex.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%